Artificial reproductive technologies and the right to the truth about genetic and biographic origins. (2017) - Poli, Ludovica
The right of ART-conceived people to know their origins emerges in any case of 'third-party reproduction', that is when the genetic material is provided, or the gestation is carried out, by a person other that the parent(s) who will take care of the resulting baby. This right has a double dimension, as it might refer to genetic origins, as well as to biographic origins. The paper explores the legal foundations of the right to genetic and biographic origins under international law and envisages possible principles to be applied in balancing it with other competing interests. It finally explains that the conditio sine qua non for a full exercise of the right to know personal origins is the awareness of the means of conception, a responsibility which rests upon the recipient parents, with only a residual role for the state.